The Relationship of Scientific Research Outputs of Higher education Institutions with technological innovation in the industrial establishment A field study of Condor (Bordj Bou-Arreridj) - Wahiba CHEBILI (Social Sciences Journal, 1970)
The survival of establishments depend largely on what achieved from technological innovation, so produce of new orimprove what exists whether on the domain of products or operations became a need that the establishments must put it apriority of their objectives. Therefore many countries have developed technological innovation through the strategies adopted,such as cooperation between them and institutions of higher education. The latter being the true generator of knowledge indeveloped countries, whether the outputs of education became especially the research one of the sources the most importantnearby the establishments, its possession mean the innovation and the invention then the technology, an idea or invention.